ANALISIS MINAT BACA TEKS NARASI PADA SISWA KELAS IV DI SD NEGERI MOJOAGUNG 01 KABUPATEN PATI - Asfiyatul Mustafidah; Suyitno; Filia Prima Artharina, S. Pd., M. Pd. (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is motivated by the fact that students' interest in reading narrative texts is still relatively low. Low here means not having one's own awareness in reading books, low attention in reading books both at school and at home, not showing pleasure in reading books and low frequency of reading books. In this context, there needs to be greater attention from all parties, including parents, to increase students' interest in reading. This study aims to analyze the interest in reading narrative texts in fourth-grade students at Mojoagung 01 Elementary School, Pati Regency and to determine the supporting factors and inhibiting factors that influence the interest in reading narrative texts in fourth-grade students at Mojoagung 01 Elementary School, Pati Regency. This research uses a qualitative research type with a descriptive analysis approach. The data sources in this study were the fourth-grade teachers, the principal, and fourth-grade students of SDN Mojoagung 01, Pati Regency. The data collection techniques used in this study were interviews and questionnaires. The data analysis method in this study consists of data reduction, data presentation and drawing conclusions. Based on the research results and discussions that have been described, it can be concluded that 7 fourth- grade students (43.75%) showed a high interest in reading narrative texts. 8 students (50%) were classified as having sufficient interest in reading. 1 student (6.25%) was included in the category of not interested in reading. Therefore, students showed an interest in reading narrative texts in the "sufficient" to "good" category.